Встреча с прошлым: Повесть / Трофимов Архипов - Архипов Трофим Архипович (Удмуртия, 1975)
Экземпляры: ф.7 (ретро) / Инвентарный номер: 30825 / Сис.шифр: К84(2Рос=Удм) / Авт.знак: А87 / ББК: 84(2Рос=Удм)